Hospital preparedness for Ebola virus disease: a training course in the Philippines - Celia Carlos; Rowena Capistrano; Charissa Fay Tobora; Mari Rose delos Reyes; Socorro Lupisan; Aura Corpuz; Charito Aumentado; Lyndon Lee Suy; Julie Hall; Julian Donald; Megan Counahan; Melanie S Curless; et al. (World Health Organization Regional Office for the Western Pacific, 2015)
Objective: To develop, teach and evaluate a training workshop that could rapidly prepare large numbers of health professionals working in hospitals in the Philippines to detect and safely manage Ebola virus disease (EVD). The strategy was to train teams (each usually with five members) of key health professionals from public, private and local government hospitals across the Philippines who could then guide Ebola preparedness in their hospitals. Methods: The workshop was developed collaboratively by the Philippine Department of Health and the country office of the World Health Organization. It was evaluated using a pre- and post-workshop test and two evaluation forms. Chi-square tests and linear regression analyses were conducted comparing pre- and post-workshop test results. Results: A three-day workshop was developed and used to train 364 doctors, nurses and medical technologists from 78 hospitals across the Philippines in three initial batches. Knowledge about EVD increased significantly (P < 0.009) although knowledge on transmission remained suboptimal. Confidence in managing EVD increased significantly (P = 0.018) with 96% of participants feeling more prepared to safely manage EVD cases. Discussion: The three-day workshop to prepare hospital staff for EVD was effective at increasing the level of knowledge about EVD and the level of confidence in managing EVD safely. This workshop could be adapted for use as baseline training in EVD in other developing countries to prepare large numbers of hospital staff to rapidly detect, isolate and safely manage EVD cases.